Migration routes of North European Reed Warblers Acrocephalus scirpaceus - Fransson, Thord; Stolt, Bengt-Olov (Ornis Svecica, 2005)
Migration routes of expanding North European Reed Warbler populations were investigated by means of more than 2,500 recoveries of birds ringed in Norway, Sweden and Finland. We found different autumn directions: from Norway SSW 195°–200°, from Sweden SSW–SW 211°–216°, and from Finland SW 220°–226°. Recoveries in Belgium showed that the autumn routes from the three countries passed over different areas at the latitude of Belgium. They converged at the Iberian Peninsula and continued in new directions through Morocco towards winter quarters in tropical West Africa (recoveries in Mauritania, Mali, Ghana, Ivory Coast and Liberia). In autumn, directions varied more in first-year than in older birds. In spring, the route was more direct and narrow than in autumn. Stopover in NW Africa, compared with the Iberian Peninsula, was more frequent in spring than in autumn. The SW directed routes of North European birds were similar to those of other West European populations, but differed from the SE directed autumn migration of the Hungarian, Slovakian and eastern Austrian populations.